The Role of Digital Tools in Qur'anic Research and Tafsir: Improving Methodology and Interpretation - Thon Thowi Hamdi; Masruhan Masruhan (Universitas Nurul Jadid, 2025)
The transformation of higher education, particularly in Islamic studies, necessitates innovation in learning and research. This study explores the role of digital tools in Qur'anic and Tafsir research, analyzing their impact on efficiency, accuracy, and interdisciplinary collaboration. Using a qualitative case study approach, data were collected through observation, interviews, and documentation, involving rectors, faculty leaders, lecturers, students, and IT teams. Findings show that successful digital integration requires strong academic literacy and technology-based methodologies. Tools like corpus analysis software, AI-driven text comparison, and digital manuscripts enhance precision in analyzing Qur'anic texts, reducing processing time and enabling deeper cross-referencing. Compared to traditional methods, digital tools improve accuracy in identifying linguistic patterns and historical interpretations. Additionally, technology fosters interdisciplinary dialogue, connecting Qur'anic studies with linguistics, history, and artificial intelligence. This study underscores the importance of bridging tradition and technology, advocating for structured frameworks to optimize digital tools in Qur'an and Tafsir research. By embracing technological advancements, Islamic studies can remain relevant, innovative, and better equipped to address contemporary academic and societal challenges.